Chapter 10: Steel Bridges - Parke, G. A. R .; Harding, J.E.; Nor Ashikin, Muhamad Khairussaleh (ICE Publishing, 2022)
Steel has been used extensively over the last 120 years to construct a large majority of the world’s greatest bridges. This chapter, on the design of steel bridges, gives an introduction to the different types of steel bridges in use, followed by guidance on the behaviour of steel plates loaded in both shear and compression. Careful attention is given to assist understanding of the load displacement behaviour of stiffened plates, which are the fundamental components of both plate girders and box girders. Steel plate girders are used extensively in the construction of medium-span bridges and steel box girders form the decks of all modern, innovative suspension bridges. The behaviour and design of bolted and welded connections is also included in this chapter, along with guidance on the fatigue appraisal of steel bridges.